School tenure and student achievement - Wen Fan (University College Dublin, UCD School of Economics, 2011)
While much empirical work concerns job tenure, this paper introduces the concept of school tenure - the length of time one student has been in a given school. I examine whether and how school tenure impacts students' output using rich cohort data on England's secondary schools. Ordinary Least Squares (OLS) estimates suggest that, on average, students benefit from longer own school tenure but suffer from that of their peers. Using the number of times the student moved school during the academic year as an instrument for school tenure to deal with potential endogeneity, the resulting Two-Stage Least Squares (TSLS) estimates suggest the effects of school tenure are positive and heterogeneous across students. While advantaged students are more likely to gain from own longer school tenure, disadvantaged ones benefit if their peers have longer tenure.
Keywords: I21; Z13; 330; school tenure; school moving; peer effects